2009
DOI: 10.3122/jabfm.2009.05.080134
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Tolerability of Low-Dose Hormone Therapy in Managing Menopausal Symptoms

Abstract: The primary indication for postmenopausal hormone therapy (HT) is to relieve the vasomotor symptoms (hot flashes, night sweats) and vaginal dryness and discomfort that often accompany the menopausal transition and beyond. These symptoms, which are attributed to the natural decline in estrogen during and after menopause, can be remedied with HT. The loss of bone mineral density (BMD) and associated skeletal fragility and increased risk of fracture are also effectively mitigated by HT in postmenopausal women.1-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
(92 reference statements)
0
17
0
Order By: Relevance
“…Getting sufficient long-term data about the multiple different medications over a significant length of time in a generally healthy population has been part of the difficulty. Langer et al 14 review what we know about low-dose therapy. Several current national recommendations suggest low-dose therapy for as little time as necessary for symptoms of menopause.…”
Section: Hormonal Problems In Family Medicinementioning
confidence: 99%
“…Getting sufficient long-term data about the multiple different medications over a significant length of time in a generally healthy population has been part of the difficulty. Langer et al 14 review what we know about low-dose therapy. Several current national recommendations suggest low-dose therapy for as little time as necessary for symptoms of menopause.…”
Section: Hormonal Problems In Family Medicinementioning
confidence: 99%
“…Results of the WHI trial revealed an increased risk of breast cancer in women who used HT; however, the women enrolled in the study were on average 12 years post menopausal (Langer, 2009). The findings of the trial are not necessarily generalizable to a younger population, but fears of adverse effects remain .…”
Section: Hormone Therapymentioning
confidence: 91%
“…Conventional HT consists of estrogen replacement with the addition of progestin for those who retain their uterus (Langer, 2009). The goal in prescribing HT is to determine the lowest dose that effectively alleviates bothersome perimenopausal and menopausal VMS (Langer, 2009 showed a similar reduction in the number of hot flashes at the 12 week period of therapy 37 compared to higher doses.…”
Section: Hormone Therapymentioning
confidence: 99%
See 2 more Smart Citations